ANALISIS DAYA SAING DAN DETERMINAN PRODUK OLAHAN NIKEL INDONESIA - Jastra Widiyanti; Saputra, Putu Mahardika Adi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Nickel is a mineral that has become popular in recent years as the electric vehicle industry has boomed. Indonesia is a country with abundant resources and reserves of raw nickel ore. This study aims to determine the export competitiveness of Indonesian processed nickel products against their exporters and the factors that influence exports of Indonesian processed nickel products. This research is included in quantitative research using secondary data. The analysis technique used is the Revealed Comparative Advantage (RCA) analysis method and panel regression analysis. The results show that in the Nickel Processed Product Commodity, Indonesia has quite good competitiveness against competing countries. In addition, the competitiveness variable, the Gross Domestic Product per capita of the destination country, and the exchange rate of the destination country have a significant positive effect on Indonesia's exports of processed nickel products. The findings of this study imply that Indonesia needs to maintain and increase its current competitiveness for nickel-processed product commodities and needs to pay attention to factors such as competitiveness, Gross Domestic Product per capita of destination countries, and destination country exchange rates to optimize Indonesia's export activities.